NOTE ON A JUVENILE INDIAN PORPOISE NEOMERIS PHOCAENOIDES (CUVIER) CAUGHT OFF CALICUT - Balan, V (Indian Journal of Fisheries, 2011)
A juvenile Indian porpoise Neomeris phocaenoides (Cuvier) nicasuring 669 mm in total-length and weighing 4520 g was caught in gillnet, off Calicut, in February 1973. The morphometric data and the diagnostic features relating to the specimen are given